2017
DOI: 10.1186/s13098-017-0249-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes of myocardial lipidomics profiling in a rat model of diabetic cardiomyopathy using UPLC/Q-TOF/MS analysis

Abstract: BackgroundDiabetic cardiomyopathy (DCM) is a serious cardiac dysfunction induced by changes in the structure and contractility of the myocardium that are initiated in part by alterations in energy substrates. The underlying mechanisms of DCM are still under controversial. The observation of lipids, especially lipidomics profiling, can provide an insight into the know the biomarkers of DCM. The aim of our research was to detect changes of myocardial lipidomics profiling in a rat model of diabetic cardiomyopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Then, we used UPLC/Q-TOF/MS analyzed approach to explore the changes of myocardial lipidomic profiles in diabetic rats. And the results manifested that the cardiac lipid metabolites have remarkable correlation with changes of cardiac function and heart mass ratio (Dong et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we used UPLC/Q-TOF/MS analyzed approach to explore the changes of myocardial lipidomic profiles in diabetic rats. And the results manifested that the cardiac lipid metabolites have remarkable correlation with changes of cardiac function and heart mass ratio (Dong et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies in DCM animal models suggested the important role of phospholipids (e.g., phosphatidylcholine and phosphatidylethanolamine) in the development of cardiac dysfunction and remodeling of DCM (Dong et al, 2017 ). We also found that berberine could protect against cardiac dysfunction induced by high caloric diet via promoting glucose transport and inhibiting cardiac lipid accumulation (Dong et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The targeted lipid library applied in the metabolomic study was based on our existing lipid library which contains 151 lipids with known structures, including 88 PCs, 27 PEs, 23 SMs, and 13 Cers. There had been examples employing the targeted lipidomic approach in studies of other diseases such as schizophrenia, diabetic cardiomyopathy, and clear cell renal cell carcinoma . The raw data from LC‐HRMS were imported to the Skyline software (Windsor, UK) for the relative quantification of the lipid species based on the retention time and the accurate mass in the constructed polar lipids database (in‐house database).…”
Section: Methodsmentioning
confidence: 99%
“…The development and progression of DbCM is associated with altered levels of specific lipid species in the myocardium, which has led to the suggestion that lipids might act as plasma-borne biomarkers for the condition. Shotgun lipidomic studies have often been used for this purpose (Han et al, 2005, 2007; Dong et al, 2017, 2018). PC, PE, and SM species are among the lipid classes identified as potential biomarkers for DbCM (Dong et al, 2017, 2018), with a number of species correlating with changes in cardiac function (Dong et al, 2017).…”
Section: Substrate Preference Of the Diabetic Heart: Glucose And Fattmentioning
confidence: 99%
“…Shotgun lipidomic studies have often been used for this purpose (Han et al, 2005, 2007; Dong et al, 2017, 2018). PC, PE, and SM species are among the lipid classes identified as potential biomarkers for DbCM (Dong et al, 2017, 2018), with a number of species correlating with changes in cardiac function (Dong et al, 2017). Specifically, the species PC[22:6/18:2], PC[22:/18:1], PC[20:4/16:1], PE[20:4/18:2], and PE[20:4/16:0] were all found to be downregulated, and PC[20:2/18:2], PC[18:0/16:0], and PC[20:4/18:0] upregulated in the myocardium of a high-sucrose/fat diet +STZ rat model (Dong et al, 2017), with some perturbations in lipid profiles (e.g., PC[20:4/18:0]) being partially reversible upon treatment with the phytochemical berberine, the active ingredient of a traditional Chinese medicine used in the treatment of diabetes (Dong et al, 2018).…”
Section: Substrate Preference Of the Diabetic Heart: Glucose And Fattmentioning
confidence: 99%